Analisis Kolaboratif dan Manajemen Pertunjukan Siswa Kelas 12 dalam Persiapan Pagelaran Seni : Studi Kasus di SMAN 14 Semarang - Cairunnisha Putri Maharanie; Utami Arsih (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study examines the dynamics of collaborative skills among 12th-grade students at SMAN 14 Semarang in preparing an arts performance using project-based learning. The main focus of this study is to analyze how performance management serves as a means of developing social competencies and to identify supporting and inhibiting factors in teamwork. The research approach used was descriptive qualitative, with data collected through participant observation, semi-structured interviews, and documentation studies of subjects selected through purposive sampling. The data analysis process was conducted interactively through stages of data reduction, data presentation, and conclusion drawing. The research findings revealed that student collaboration developed rapidly in aspects of interpersonal communication, role allocation, and conflict resolution skills. The presence of peer leadership and the availability of practice facilities were key drivers of the project's success. This arts performance served as an effective pedagogical instrument for building students' soft skills in a tangible way, while simultaneously strengthening the relevance of the arts and culture curriculum in education.